Improvement of quality of pedagogical dough from a course of the higher mathematics on a subject "integral calculus" - Larisa V. Limanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
One of ways of control of knowledge is testing of pupils. The purpose of this work is improvement of quality of pedagogical dough on the subject "Integral calculus" of a course of the higher mathematics which is applied to an assessment of knowledge of students at the first year of SAMGTU. One of the main characteristics of dough - reliability was for this purpose investigated. The coefficient of reliability is calculated by means of three formulas: on a variation of test tasks (formula KR-20); with use of average coefficient of correlation of all tasks among themselves; on Spirmena- Brown's formula. Research of reliability showed need of increase in number of tasks according to a frequency rate formula.